Online Impulsive Buying Behavior (Oibb) Influenced By Hedonism, Resource Availability, And Shopping Convenience Moderated By The Ease Of Using Digital Payment Methods - Elisabeth Krisna Dhewayanti (UNIVED Press, 2024)
This research focuses on the influence of hedonism, resource availability, and shopping convenience online impulsive buying behavior (OIBB), moderated by ease of use of digital payment method. Data collected by distributing questionnaires viaa online to 356 respondents. A total of 340 respondents were selected to be the sample because they fit the specified respondent criteria. The data obtained was analyzed using the PLS-SEM method, and processed using SmartPLS software version 4.0. The results of this research show that hedonism and convenience of shopping directly have a positive and significant influence on online impulsive buying behavior. While the availability of resources (money) does not significantly influence online impulsive buying behavior. In the moderation relationship, ease of use of e-wallets is proven to strengthen the relationship between hedonism and online impulsive buying behavior, but can decrease the relationship between shopping convenience and online impulsive buying behavior. Meanwhile, ease of use of e-wallets has no influence on the relationship between availability of funds and online impulsive buying behavior.